Salt Solutions Demonstrate Antibacterial Activity Against Selected Pathogenic Bacteria: Larutan Garam Menunjukkan Aktivitas Antibakteri Terhadap Bakteri Patogen Terpilih - Yazni Rahma Dewi; Chylen Rini (Academia Open, 2025)
General Background: Antibacterial agents are widely studied to control bacterial growth in medical and food applications. Specific Background: Himalayan Pink salt and Krosok salt contain sodium chloride with varying salinity levels and are investigated for antibacterial activity against Lactobacillus acidophilus and Pseudomonas aeruginosa. Knowledge Gap: Comparative evidence regarding antibacterial responses between different salt types and concentration levels remains limited. Aims: This study compares antibacterial activity of Himalayan Pink salt and Krosok salt solutions at concentrations of 5%–25% against both bacteria. Results: Sterile distilled water produced no inhibition, while ciprofloxacin generated inhibition zones of 4.43 mm against Lactobacillus acidophilus and 22.69 mm against Pseudomonas aeruginosa. Both salt solutions showed increased inhibition as concentration increased. Against Lactobacillus acidophilus, both salts produced weak inhibition ranging from 0.03 mm to 0.35 mm. Against Pseudomonas aeruginosa, Himalayan Pink salt produced inhibition diameters from 5.53 mm to 10.95 mm, while Krosok salt produced 5.56 mm to 10.55 mm. Novelty: This study demonstrates comparable antibacterial response patterns between two natural salt types across concentration variations. Implications: The findings provide reference data supporting saline solutions as alternative antibacterial materials and contribute to antimicrobial research. Highlights: Increasing Salinity Concentration Produced Larger Inhibition Zones in Both Tested Microorganisms. Ciprofloxacin Generated Strong Bacterial Suppression for One Tested Species and Weak Suppression for Another. Comparable Inhibition Patterns Were Observed Between Both Tested Mineral Salt Types Across Concentration Levels. Keywords: Himalayan Pink Salt, Krosok Sal, Antibacterial Activity, Lactobacillus Acidophilus, Pseudomonas Aeruginosa